The External and Internal Shame Scale (EISS): Turkish Adaptation Study - Merve Gür; Burhan Çapri (Sakarya Üniversitesi Eğitim Fakültesi Dergisi, 2024)
The aim of this research is to carry out the Turkish adaptation, validity and reliability studies of the "External and Internal Shame Scale”, which was developed to measure the two sub-dimensions of shame, internal and external shame, at once. The sample of the research consists of 434 university students studying at Mersin University and other state universities. In order to provide evidence for the construct validity of the scale, confirmatory factor analysis (CFA) and criterion-related validity studies were conducted and the correlation values between the sub-factors were examined. When the correlation values between CFA and sub-factors and the results of the criterion-related validity study were examined, it was seen that the scale had sufficient construct validity. In order to determine the reliability of the scale, Cronbach's alpha internal consistency reliability coefficient, item-total test correlation (ITTC) coefficient and test-retest correlation coefficient were calculated. Cronbach's alpha internal consistency coefficients were calculated as .77 for internal shame sub-factor, .76 for external shame sub-factor and .87 for total shame. Similarly, ITTC coefficients were found to be between .49 and .64 for the internal shame sub-factor, between .49 and .62 for the external shame sub-factor, and between .56 and .71 for the total shame. In addition, the test-retest reliability coefficients were calculated as .79 for the internal shame subscale and .78 for the external shame subscale. The data obtained showed that the adapted External and Internal Shame Scale (EISS) is a valid and reliable measurement tool for measuring the internal, external and total shame of university students.